2008
DOI: 10.1016/j.ica.2007.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II) complexes of 1,10-phenanthroline: Synthesis and X-ray crystal structure determination

Abstract: Two palladium(II) complexes, [Pd(phen) , in acetonitrile and water, respectively. The structures of both complexes are based on a Pd(phen) 2+ metal core, with two acetonitrile molecules binding in a monodentate fashion in complex 1 and two hydroxo bridges holding together two cores to form a dimer in complex 2. Additionally, both complexes present a hydrogen bonded 3-D network involving the triflate anions in 1, and water and triflate anions in 2. Both complexes have been characterized by infrared and 1 H NMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…The N 2 O 2 donor sets of the two chelating Schiff base ligands in the equatorial plane around Pd1 adopt a slightly distorted square-planar coordination geometry. The Pd1-N1 and Pd1-O1 distances (Table 1) are typical of square-planar Pd II complexes, and compare well with those observed in other closely related Pd II complexes (Adrian et al, 2008;Bahron et al, 2014;Wan Ibrahim & Shamsuddin, 2012). The bite angle of the iminomethylphenolate chelate, N1-Pd1-O1 is 88.48 (8) , which is also similar to that in a related Pd II complex (Bahron et al, 2014).…”
Section: Structural Commentarysupporting
confidence: 77%
“…The N 2 O 2 donor sets of the two chelating Schiff base ligands in the equatorial plane around Pd1 adopt a slightly distorted square-planar coordination geometry. The Pd1-N1 and Pd1-O1 distances (Table 1) are typical of square-planar Pd II complexes, and compare well with those observed in other closely related Pd II complexes (Adrian et al, 2008;Bahron et al, 2014;Wan Ibrahim & Shamsuddin, 2012). The bite angle of the iminomethylphenolate chelate, N1-Pd1-O1 is 88.48 (8) , which is also similar to that in a related Pd II complex (Bahron et al, 2014).…”
Section: Structural Commentarysupporting
confidence: 77%
“…As shown in Figure 2, the Pd II metal centre has a cis-planar coordination by the two phenolic oxygen atoms and two imine nitrogen atoms. The Pd-O distances are in the range 1.979(3) -2.008(4) Å with Pd-N distances 1.981(3) -2.014(3) Å, which are typical of the square-planar Pd II complex of Schiff base ligand [7]. The bond angles around Pd II ions suggested that the complex has a distorted square-planar geometry as indicated by the angles O-Pd-O in the range 79.66(11) -80.54(16), O-Pd-N in the range 92.14(13) -92.95 (11) and N-Pd-N in the range 94.92(12) -94.95(15), deviating substantially from that expected for a regular squareplanar geometry.…”
Section: X-ray Crystallography Analysismentioning
confidence: 95%
“…The bond distances and bond angles in the title complex are normal (Allen et al, 2002). The Pd1-O and Pd1-N bond lengths of 1.981 (2) and 2.039 (2)Å, respectively, in a square planar geometry are typical of square planar Pd(II) of Schiff bases (Adrian et al, 2008). The dihedral angle between the benzene rings is 76.5 (2)°.…”
Section: S1 Commentmentioning
confidence: 95%
“…For related structures, see: Adrian et al (2008); Wan Nazihah Wan Ibrahim et al (2008); Chen & Xia (2009). For bond-length data, see: Allen et al (2002).…”
Section: Related Literaturementioning
confidence: 99%